2013
DOI: 10.1039/c3fd00120b
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly of biomolecular soft matter

Abstract: Self-assembly programmed by molecular structure and guided dynamically by energy dissipation is a ubiquitous phenomenon in biological systems that build functional structures from the nanoscale to macroscopic dimensions. This paper describes examples of one-dimensional self-assembly of peptide amphiphiles and the consequent biological functions that emerge in these systems. We also discuss here hierarchical self-assembly of supramolecular peptide nanostructures and polysaccharides, and some new results are rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
68
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(69 citation statements)
references
References 114 publications
1
68
0
Order By: Relevance
“…12 Ren et al also found that the content of HCNFs strongly depended on the type of catalytic supports and ratio of Cu/support. 12 At present, preparing helical nanofibers, [13][14][15][16] such as HCNFs, using novel catalyst has attracted great interest from researchers in the field of synthesis and related nanomaterials. [17][18][19] However, few works in the literature are concerned with the interaction between the ZnO matrix and Cu nanocrystals in helical fiber synthesis, which may have a great influence on the catalysts' properties.…”
Section: Introductionmentioning
confidence: 99%
“…12 Ren et al also found that the content of HCNFs strongly depended on the type of catalytic supports and ratio of Cu/support. 12 At present, preparing helical nanofibers, [13][14][15][16] such as HCNFs, using novel catalyst has attracted great interest from researchers in the field of synthesis and related nanomaterials. [17][18][19] However, few works in the literature are concerned with the interaction between the ZnO matrix and Cu nanocrystals in helical fiber synthesis, which may have a great influence on the catalysts' properties.…”
Section: Introductionmentioning
confidence: 99%
“…Random-coil supramolecular polymers were studied by Meijer and co-workers, yielding an interesting class of materials with properties similar to those of regular polymers but with the dynamics of supramolecular assemblies. 58 The second class involves the formation of one-dimensional nanoarchitectures with a high degree of internal order (ordered supramolecular polymers) and was developed and extensively studied in the laboratories of Stupp, 59–62 Aida, 63 and others. 64,65 Ordered supramolecular polymers all share a common feature: The self-assembly of the monomers is driven by at least one type of anisotropic interaction, typically hydrogen-bonding or π−π interactions.…”
Section: Bioinspired Supramolecular Polymers: Structure and Assemblymentioning
confidence: 99%
“…Adding a hydrophobic tail to one end of a peptide sequence resulted in the formation of a peptide amphiphile (PA) (Figure 3b). 59–62 This hydrophobic tail renders the peptide insoluble in water, and as a result, the monomers aggregate upon dispersion in aqueous solutions. Two domains in the peptide sequence prevent the aggregates from forming amorphous precipitates.…”
Section: Bioinspired Supramolecular Polymers: Structure and Assemblymentioning
confidence: 99%
“…These structures were too short, with lengths varying from 0.5 to 2 ”m, to entangle with each other, thus no three-dimensional network enabling solvent trapping could be formed 50. It has been previously reported that by increasing the attraction energy, infinite sheets of stacked ribbons are formed, instead of individual fibers 51.…”
mentioning
confidence: 98%